Collective and synchronous dynamics of photonic spiking neurons - Takahiro Inagaki (Nature Portfolio, 2021)
Neuromorphic devices take inspiration from spiking dynamics of neurons in the brain. Here, the authors demonstrate synchronized spiking dynamics in 240 photonic artificial neurons, each of which is implemented with a pair of antisymmetrically coupled degenerate optical parametric oscillators.